The princess diaries 2 royal engagement - Marshall, Garry; Andrews, Julie; Hathaway, Anne, 1982-; Elizondo, Hector; Rhys-Davies, John.; Matarazzo, Heather, 1982-; Cabot, Meg.; Walt Disney Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) ([United States] : Walt Disney Home Entertainment ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2004)
Princess Mia has just graduated college. She is soon going to take over as Queen of Genovia from her grandmother, Queen Clarisse. However, Mia learns that she must marry in 30 days or forfeit the crown of Genovia to another rightful heir, Nicholas Devereaux. His uncle, Vicount Mabrey is really the one who wants Nicholas to be King. Not trusting Nicholas, Mia picks a decent guy who's sweet and charming and likeable, but can she go through with the wedding to someone she doesn't really love? Will Mia follow her heart or sacrifice for her country?
Based on the characters created by Meg Cabot.
Special features: royal bloopers; deleted scenes; "Breakaway" music video by Kelly Clarkson; the PD2 makeover - hip tips on how to capture Princess Mia's look; find your inner Princess - a set-top personality quiz; making a return engagement - a behind-the-scenes look at the cool music in the movie, hosted by Raven; a Julie Andrews & Garry Marshall commentary.
Director of photography, Chales Minsky ; editor, Bruce Green ; music, John Debney ; costume designer, Gary Jones ; production designer, Albert Brenner.
Julie Andrews, Anne Hathaway, Hector Elizondo, John Rhys- Davies, Heather Matarazzo, Chris Pine, Callum Blue, Kathleen Marshall, Tom Poston.
MPAA rating: G.
DVD.
Keywords: Princesses -- Drama; Betrothal -- Drama; Inheritance and succession -- Drama; Feature films; Video recordings for the hearing impaired